Robot‐assisted versus navigated transpedicular spine fusion: A comparative study. Issue 2 (26th January 2023) - Romagna, Alexander; Sperker, Sarah; Lumenta, Christianto; Tomasino, Andre; Schwartz, Christoph; Lehmberg, Jens; Zausinger, Stefan; Schul, David
Abstract: Background: The aim of this study was to compare the intraoperative and postoperative outcomes between a robot‐assisted versus a navigated transpedicular fusion technique. Methods: This retrospective analysis included patients who underwent transpedicular posterior fusion of the spine due to trauma, pyogenic spondylodiscitis and osteoporosis. Surgery was done either with a robot‐assisted or a percutaneous navigated transpedicular fusion technique. The outcome analysis included the duration of surgery, the radiation exposure, the postoperative screw position and complications. Results: A total of 60 patients were operated and 491 screws were analysed. No statistical difference was seen in the applied cumulative effective radiation dose per patient. The radiological assessment revealed a more accurate screw placement with robot assistance. A learning curve could be observed in robot‐assisted fusion. Conclusion: Robot‐assisted and navigated transpedicular fusion techniques are both effective and safe. Robot‐assisted transpedicular spine fusion goes along with higher placement accuracy but its implementation needs an adequate learning curve.